Characterizations of groups with almost layer-finite periodic part - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Construction of the set of finite subgroups of the form $L_g = \langle a, a^g\rangle$ in Shunkov’s groups is studying. As a corollary ofthis result follows two characterizations of groups with an almost layer-finite periodic part.